2016
DOI: 10.1111/eea.12445
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of Lactobacillus johnsonii CRL1647 metabolites for biological control of Musca domestica

Abstract: The house fly, Musca domestica L. (Diptera: Muscidae), is a key problem in animal producing and rearing areas. Currently, the use and abuse of chemical pest‐control compounds has generated resistance in M. domestica and, hence, new approaches are required. In this work, the potential entomopathogenic activity of Lactobacillus johnsonii Fujisawa et al. CRL1647 was evaluated against M. domestica, under laboratory conditions. Bioassays were done for three consecutive years using bacterial cell suspensions (CS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…In this study, we investigated the ability of L. pseudomesenteroides cells and cell-free extracts to inhibit the survival of our three target insects via the oral and septic infection routes. Although lactic acid bacteria are known to interfere with the growth of phytopathogenic bacteria and fungi [59,60], and also entomopathogenic bacteria [61], little is known about their potential as biocontrol agents against insect pests [62].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the ability of L. pseudomesenteroides cells and cell-free extracts to inhibit the survival of our three target insects via the oral and septic infection routes. Although lactic acid bacteria are known to interfere with the growth of phytopathogenic bacteria and fungi [59,60], and also entomopathogenic bacteria [61], little is known about their potential as biocontrol agents against insect pests [62].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality showed direct proportionality with increasing the exposure time and dose concentrations ( Table 2 ). Torres et al, [ 17 ] had reported that organic acids produced by L. johnsonii CRL 1647, exert pupicidal and larvicidal effects on M. domestica . Gupta et al [ 18 ] had also reported in vivo evaluation of toxic effect of antimicrobial peptides isolated from L. plantarum LR/14 on D. melanogaster , DNA fragmentation, and premature apoptosis, confirming that the peptides have a dose-dependent toxic property.…”
Section: Discussionmentioning
confidence: 99%
“…LAB are also exhibiting inhibitory potential against pathogenic fungi, namely, Aspergillus flavus and Aspergillus fumigatus [ 16 ]. Some LAB species, such as Enterococcus durans, Lactobacillus plantarum , and Lactobacillus johnsonii , also have interesting applications for biocontrol of disease-causing biological vectors, viz, C. quinquefasciatus (Mosquitoes), Drosophila melanogaster (Common fruit fly), and Musca domestica (Housefly), respectively [ 17 , 18 , 19 ]. Lactiplantibacillus plantarum (formerly known as Lactobacillus plantarum ) [ 20 ] is a potent LAB specie that is evaluated in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Before the start of the bioassay, Bacillus cell viability was determined after 24 h of incubation (Table 2). Different cohorts of houseflies maintained under laboratory conditions were used for biocontrol assays (Torres et al, 2016). Oviposition and larval development were encouraged using a substrate named DL: 34% wheat bran, 1% whole milk powder, and 65% tap water (wt/vol) (a milk diet modified from Ruiu et al, 2006).…”
Section: Evaluation Of Entomopathogenic Effectmentioning
confidence: 99%
“…Several microorganisms have been studied for their entomopathogenic activity (Mwamburi et al, 2010; Faten et al, 2011; Zimmer et al, 2013); however, except for B. thuringiensis , few studies have analyzed the use of these Gram‐positive bacteria as biocontrol alternatives against the housefly. Our working group previously reported the insecticidal effect of Lactobacillus johnsonii Fujisawa et al CRL1647 (Torres et al, 2016). The organic acids synthesized by this bacterium significantly inhibited growth of housefly larvae and pupae.…”
Section: Introductionmentioning
confidence: 99%